Going for the green : prepare your body, mind, and swing for winning golf - Gilchrist, Gary; Hill, Susan , 1962-; Troesch, Jeff (Sterling, 2009)
Teaches golfers how to master the mental, physical and mechanical aspects of the game. This book reveals a technique of varying intensity and volume of training, as used by Tiger Woods